MARKETING ANALYTICS IN THE ERA OF DIGITAL-BASED MARKETING STRATEGY - Hidayati, Arifah; Susanti, Evi; Jamalong, Ahmad; Ginting, Dafid; Suwanto, Witri; Arifin, Ardian (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This groundbreaking study delves into the intricate realm of digital marketing analysis, which entails the systematic collection and scrutiny of data pertaining to digital marketing endeavors. With a novel focus on elucidating the economic ramifications of digital marketing on sales augmentation, the research employs an innovative approach. Leveraging an exhaustive literature review drawn from national and international journals, the study illuminates the transformative impact of digital marketing, particularly in the context of burgeoning online markets. Employing the PRISMA methodological framework, researchers meticulously navigated through the identification, screening, feasibility, and finalization phases to distill a comprehensive understanding of the topic's scope. With a laser focus on "Marketing Analytics," the study hones in on publications resonating with this thematic emphasis, culminating in the identification of 330 pertinent publications devoid of duplicates. Delving deeper into the findings, the study unveils a notable surge in sales success amidst the Covid-19 era, underscoring the pivotal role of digital marketing in navigating unprecedented market dynamics. Furthermore, the research uncovers a nuanced interplay between various elements of the e-marketing mix e-product, e-price, and e-promotion and their influence on e-trust, offering valuable insights into consumer behavior in digital marketplaces. As the study draws to a close, it advocates for a visionary paradigm shift in digital marketing strategies, emphasizing the imperative of enhancing customer engagement and trust-building initiatives. Ultimately, the research underscores the indispensability of digital marketing in contemporary business landscapes, reaffirming its efficacy in fostering consumer engagement, driving sales, and nurturing enduring brand-consumer relationships.